The Carrying of Capacity of the Pangkal Babu Mangrove Forest on the Abundance of Fish Resources and the Economy of the People of Tungkal Satu Village, Tanjung Jabung Barat - Tedy Azmi Nasution; Tedjo Sukmono; Rifli Rindes; Hutwan Syarifuddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
The Pangkal Babu Mangrove Forest has an important role in a fish habitat that is closely related to the livelihoods of fishermen so it has an overall economic relationship. This study aims to analyze the condition of mangrove forests, the triangulation relationship between mangrove forests and fish resources, and the community's economy as well as forms of local wisdom in protecting and preserving mangrove forests. This research was conducted in the Pangkal Babu Mangrove forest area, Tungkal Ilir District, West Tanjung Jabung Regency. The method in this study is a survey method. The sampling technique for the condition of the mangrove forest was using the Line Transect Plot method at 3 different stations. The data analyzed included the density of mangrove forests, fishery resources, the economy, and the local wisdom of the community. The results showed that at station I the condition of mangrove vegetation in Pangkal Babu was in moderate criteria with 1,467 trees/ha, station II was in very dense criteria with 3,367 trees/ha, and station III was in moderate criteria with 1,000 trees/ha. Fishery production for 5 years is 93,221 kg with many trips of 2,115 and a CPUE value of 44.13 kg/trip. Fishery production has exceeded the sustainable potential both biologically (MSY = 82,297 kg) and economically (MEY = 82,296 kg). The value of the coefficient of determination (R2) is 0.82 or 82%, which indicates that the fluctuation in fishery production is caused by the area of mangrove forests by 82%.